1985
DOI: 10.1051/rnd:19850214
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotéines plasmatiques du veau préruminant

Abstract: Summary. Plasma Introduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…During the postprandial period, a large increase in the plasma concentrations of calf chylomicrons and VLDL was noted from 7 h after meal intake. Furthermore, the fatty acid composition of triacylglycerols of these particles was then representative of the dietary fatty acid composition (Bauchart & Levieux, 1985). These results provided evidence that in the calf fed on curdled milk substitute peak lipid absorption was 5-7 h later than that in conventional singlestomached animals.…”
Section: Lipid Digestion In Ruminantssupporting
confidence: 53%
See 1 more Smart Citation
“…During the postprandial period, a large increase in the plasma concentrations of calf chylomicrons and VLDL was noted from 7 h after meal intake. Furthermore, the fatty acid composition of triacylglycerols of these particles was then representative of the dietary fatty acid composition (Bauchart & Levieux, 1985). These results provided evidence that in the calf fed on curdled milk substitute peak lipid absorption was 5-7 h later than that in conventional singlestomached animals.…”
Section: Lipid Digestion In Ruminantssupporting
confidence: 53%
“…Utilizing electromagnetic blood-flow measurement, we have shown that in calves fed on a milk diet which curdles in the abomasum, portal blood flow rapidly increases 1 h after meal intake, probably in response to the intestinal absorption of glucose (Durand et al 1988). Hyperglycaemia noted 46-90 min after intake increased plasma insulin which stimulated the degradation of plasma triacylglycerols by lipoprotein lipase (EC 3.1.1.34; LPL; Bauchart & Levieux, 1985). This was followed by the clot formation in the abomasum decreasing portal blood flow for the next 4 h due to the drop in mesenteric blood flow (which constitutes 65% of the portal blood flow) following a lack of nutrient absorption during this period.…”
Section: Lipid Digestion In Ruminantsmentioning
confidence: 99%
“…In all three groups concentrations of p-carotene in VLDL and LDL are higher than in cows and bulls. This is due to a higher concentration of these fractions in suckling calves (BAUCHART and LEVIEUX 1985) and in cows during the dry period, where RAPHAEL et al (1973) found a two-to-three fold increase in VLDL. The existence of chylomicrones in suckling calves contrary to mature cattle has already been reported by CHAPLIN and PALMQUIST (1971).…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, the higher and faster cellular incorporation from Pyr-met-Chol-labelled purified LDL than from Pyr-met-Chol-labelled purified HDL ( Fig 2B ) is also indicative of an interaction with the corresponding specific receptors, and this is consistent with the reported overexpression of LDL receptors in the PC-3 cells [ 21 , 35 ]. However, when PC-3 cells are incubated in the presence of total serum, the relative contributions of LDL- and HDL-mediated incorporation routes are expected to be fairly comparable since HDL are present in foetal calf serum in somehow higher (2–3 fold) amounts than LDL [ 54 ].…”
Section: Discussionmentioning
confidence: 99%